Towards an European good governance barometer - Gaggi, Silvia; Sessa, Carlo (Ökologisches Wirtschaften - Fachzeitschrift, 2012)
Good governance is a key element in achieving sustainable development. But how are both concepts linked in the practice of measuring sustainable development? Experts and representatives of the civil society cooperated to define good governance criteria for sustainable development indicators.